Effects of Nitrogen Addition on Plant Properties and Microbiomes Under High Phosphorus Addition Level in the Alpine Steppe - Dong, Junfu; Cui, Xiaoyong; Niu, Haishan; Zhang, Jing; Zhu, Chuanlu; Li, Linfeng; Pang, Zhe; Wang, Shiping (Frontiers in Plant Science, 2022)
Nitrogen (N) addition can increase the vegetative growth, improve the plant production, and restore the degraded terrestrial ecosystems. But it simultaneously aggravates the soil phosphorus (P) limitation for plant growth, thus affecting its positive effects on ecosystems. However, if the P-limitation was lessened or eliminated, how plants and soil microorganisms will change is still unknown. We explored the effects of three levels of N addition (0, 7.5, 15 g.N.m-2.yr-1) on plants and microorganisms under high P addition level (13.09 g.P.m-2.yr-1) in the Tibetan alpine steppe. We found that the soil microbial community composition had no significant difference between different N addition level, and the soil AN and AP had significant effect on the PLFA composition. The abundance of the core PLFAs (i.e., 16:1ω7c, 16:0, a17:1, i 17:0, 18:1ω9c, and 18:1ω7c) also remained unchanged after N addition, and microbes at individual, population and community level were all correlated with SOM, AK, AN, and pH. Conversely, plant biomass and nutrient content shown linear trends with increasing N addition, especially the dominant plant population. Specifically, the biomass and plant tissue N content of Gramineae, as well as the total N content of aboveground biomass were all improved by N addition. They were correlated with soil ammonium and AP. The structural equation modeling (SEM) demonstrated that N addition had direct negative effect on soil microbial biomass, but indirect positive effect on aboveground biomass via soil ammonium. These findings clarify the the responses of plants and microorganisms to N addition in the Tibetan alpine steppe, which helps us to find solutions to face global climate changes.